Identification of Novel Determinants of Neutralization Epitope Shielding for Hepatitis C Virus in Vitro - Garazi Peña Alzua; Anne Finne Pihl; Anna Falden Offersgaard; Rodrigo Velázquez-Moctezuma; Elias Honeroed Augestad; Ulrik Fahnøe; Christian Kjaerulff Mathiesen; Mansun Law; Jannick Prentoe; Jens Bukh; Judith Margarete Gottwein (Proceedings, 2020)
Epitope shielding is suggested as an important mechanism mediating the escape of hepatitis C virus (HCV) from host-neutralizing antibodies (nAb). [...]